Generation of Plvap-CreER and Car4-CreER for genetic targeting of distinct lung capillary populations. (December 2022) - Zhang, Zhenqian; Zhou, Bin
Abstract: It has been reported recently that there are two distinct subpopulations of capillary endothelial cells in the mammalian lungs: gCap (general capillary) and aCap (aerocyte). They are identified by two unique markers, respectively: plasmalemmal vesicle-associated protein (PLVAP) and carbonic anhydrase IV (CAR4). Here, we report two novel knock-in mouse lines Plvap-CreER and Car4-CreER, which genetically target gCap and aCap, respectively. Induced by tamoxifen, the Plvap-CreER and Car4-CreER alleles mediate specific and efficient Cre- lox P recombinations in PLVAP +  gCap and CAR4 + aCap, respectively, in the lungs. These two mouse lines are useful genetic tools to investigate cell fates and functions of PLVAP + and CAR4 + cells in lung homeostasis, injury and repair.